THE STATE OF GENERAL CHEMICAL EDUCATION AND THE INITIAL METHODOLOGICAL AND THEORETICAL BASIS OF THE RESEARCH - Tadjieva Khosiyat Sultanovna (Modern American Journals, 2025)
Medical education is a crucial element of the continuing education system in Russia, aimed at ensuring public health and preparing people for a healthy lifestyle. By the end of the 20th century, society's utilitarian and pragmatic attitude toward nature led to an environmental crisis and a deterioration in the socioeconomic situation, leading to increased morbidity and mortality, and a decline in life expectancy in many regions of the country. Drug and alcohol addiction, as well as AIDS, have reached alarming levels, especially among young people. Consequently, fundamentally new demands have emerged in modern society for the national education system, including the medical education system, and new directions for its reform. In the context of globalization and the current state of society, the priority of a sustainable development model and universal human values has been proclaimed, reflected in the goals and fundamental principles of secondary and higher education, as well as enshrined in state regulatory documents.